Impact of Accelerate Pheno System on Time to Antimicrobial Stewardship Intervention in Patients with Gram-Negative Blood Stream Infections. (4th October 2017) - Elliott, Gerald; Postelnick, Michael; Martin, David; Barr, Viktorija; Malczynski, Michael; Aljefri, Doaa; Sutton, Sarah; Zembower, Teresa; Qi, Chao
Abstract: Background: Rapid diagnostic tests in combination with antimicrobial stewardship interventions have been shown to improve antimicrobial therapy-related outcomes in patients with blood stream infections (BSIs). The Accelerate Pheno™ System (APS) has a potential advantage over many currently approved rapid diagnostic tests in that it can quickly provide both identification and antimicrobial susceptibility (AS) information. This study aimed to explore the impact of utilization of the APS when compared with VITEK-2 on time to simulated antimicrobial stewardship service intervention (ASTEW-I) in patients with Gram-negative BSIs. Potential impact of availability of ASTEW-I based on time of day was also examined. Methods: Consecutive patients with Gram-negative rod blood stream isolates were enrolled during a 3 month time frame (February-May 2017). The standard of care (SOC) laboratory protocol consisted of matrix-assisted laser desorption ionization time of flight (MALDI-TOF) for pathogen identification and VITEK-2 for AS results. Antimicrobial susceptibility reporting on the electronic health record was performed once daily in the morning. The isolates that were analyzed through SOC measures were also simultaneously tested on the APS. Time to ASTEW-I was simulated utilizing AS reporting time and availability of personnel for ASTEW-I based on time of day. Results: 27 patients with positive blood cultures for Gram-negative rods were enrolled in the study. Mean decrease in time to simulated ASTEW-I with APS was 18 hours (95% CI 11.5–24.6) for 8 hour stewardship coverage. When stewardship coverage was extended to 16 hours, the mean decrease in time to ASTEWI-I with APS was 21.4 hours (95% CI 14.3–28.5). Both time differences were found to be statistically significant ( P < 0.001). Conclusion: In a cohort of patients with Gram-negative bacteremia, when compared with SOC, ASTEW-I guided by APS significantly shortened the time to potential antimicrobial optimization. This improvement occurred even when antimicrobial stewardship support was limited to an 8 hour work day. Disclosures: C. Qi, Accelerate Diagnostics: Investigator, Research support